The long game: a longitudinal assessment of top ranked male and female golfers ranking trajectories - Koenigsberg, A.; Pilgrim, J.; Meyer, T.; Baker, J. (International Journal of Golf Science, 2023)
Success in professional golf is linked to the attainment of a top 100 world ranking. However, little is known regarding the career ranking pathways of top 100 golfers. The aim of this study was to investigate the career ranking pathways of top 100 ranked male and female professional golfers from different regions. Descriptive statistics were reported for the age that 287 male and 183 female golfers reached career ranking milestones. Golfers were assigned to one of three regional groups: Americas, Europe, and AAO (Asia, Africa, Oceania). Descriptive statistics were reported for ranking milestones and one-way ANOVAs used to investigate gender and regional differences. Overall, females reached ranking milestones at significantly younger ages and in less time than males. Differences were also found in the ages that golfers from different regions reached ranking milestones. These findings may assist coaches and national sport organisations to establish statistical benchmarks to inform athlete identification and development activities as well as career planning for emerging golfers.